Dynapenic abdominal obesity is associated with negative clinical outcomes in older patients with type 2 diabetes: a prospective cohort study - Mileni Vanti Beretta; Ticiana da Costa Rodrigues; Thais Steemburgo (Geriatrics, Gerontology and Aging)
Objective: To evaluate the association between dynapenic abdominal obesity (DAO) and the following negative outcomes in older patients with type 2 diabetes (T2D): prolonged length of stay (LOS), readmission within 30 days, in-hospital mortality, and mortality within 1 year after hospital discharge. Methods: This prospective cohort study included hospitalized older patients with T2D. DAO was defined as a combination of abdominal obesity (high waist circumference [WC]: ≥ 102 cm for men and ≥ 88 cm for women]) and dynapenia (reduced hand grip strength [HGS]: < ≤27 kg for men and < 16 kg for women]). The association between clinical outcomes and DAO was evaluated using multivariate analyses adjusted for confounders. The Kaplan-Meier curve was used to compare 1-year survival in the presence of DAO. Results: We included 309 patients with T2D (mean age 73.3 ± 6.4 years; 50.5% female; 32.4% with DAO). In multivariate analyses, patients with DAO had a 5.29- and 4.71-fold increase in LOS (≥ 14 days) and 1-year mortality than those without DAO, respectively. Moreover, patients with DAO had a higher risk of 1-year mortality (log-rank test, p < 0.05). Conclusions: Older patients with T2D and DAO are more likely to have prolonged hospitalization and 1-year mortality compared to those without DAO.